Prophylactic ilioinguinal neurectomy: Can it prevent chronic groin pain after Lichtenstein inguinal hernia repair? - Joshi, Arbin (Journal of Kathmandu Medical College, 2016)
Background: Contrary to the previous belief, division of the ilioinguinal nerve prophylactically during mesh repair has been practiced to reduce the incidence and intensity of persistent postoperative pain after hernia repair. Objectives: To evaluate whether prophylactic ilioinguinal neurectomy prevents chronic groin pain after primary Lichtenstein hernia repair.Methods: Patients undergoing elective open mesh repair of inguinal hernia were randomized in two groups; nerve excision and nerve preservation group by opaque envelope method. Fifty cases were included in each group. A telephone interview was conducted after three months of the surgery. Pain scoring was done with Numeric Pain Intensity Scale and its effect in daily activities was measured with Patient Disability Index.Results: Forty-four patients in excision group and 45 in preservation group satisfied the inclusion criteria. Nine (20%) in the previous group and 16 (34.78%) in the latter group had chronic pain (p=0.113). Mean severity score in patients who had pain was significantly high in preservation group (2.22 versus 3.31, p=0.039). The incidence of scrotal numbness was higher in excision group (20% versus 13.3%, p=0.370).Conclusion: Though insignificant reduction in incidence of chronic groin pain was observed after division of ilioinguinal nerve, significant reduction in the intensity of the chronic pain especially during activities related to home and during self care has been shown.Journal of Kathmandu Medical College, Vol. 4, No. 2, Issue 12, Apr.-Jun., 2015, Page: 39-44